Naming Nature: The Clash Between Instinct and Science - E. N. Anderson (Ethnobiology Letters, 2010)
Review of Naming Nature: The Clash Between Instinct and Science. Carol Kaesuk Yoon. 2009. W.W. Norton, New York. Pp. 344, index, bibliography, illustrations. $27.95 (cloth). ISBN 9780393‐061970.